Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.6023/cjoc202010028
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Crystal Structure, and Fungicidal Activity of L-Carvone Derivatives Containing an Oxime Ester Moiety

Abstract: L-Carvone is a natural product with fungicidal activity, which can be used as a lead compound for screening new fungicides. A series of L-carvone derivatives containing an oxime ester moiety were synthesized by splicing active substructure strategy with L-carvone as the lead compound. The structures of the L-carvone derivatives were characterized by IR, 1 H NMR, 13 C NMR and HRMS analyses. The antifungal activities of these compounds were evaluated against five plant pathogenic fungi, namely Sclerotinia sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As a natural and sustainable forest product-bearing carbonyl, carvone has been found in the seed essential oils of Anethum graveolens [9], Mentha spicata [10,11], and Carum 2 of 12 carvi [12], and its diverse pharmacological activities have been reported [13], such as antifungal [14][15][16][17], antioxidant [18], anti-inflammatory [19], and anticancer activities [20,21]. Moreover, it was discovered that the original skeleton of carvone could serve as an available pharmacophore for bioactive compounds [22][23][24][25][26]. Moreover, thiazolinone-hydrazone derivatives showed various biological activities, including antifungal [27], antitrypanosomal [28,29], insecticidal [30,31], antiproliferative [32], and α-glucosidase inhibition activities [33].…”
Section: Introductionmentioning
confidence: 99%
“…As a natural and sustainable forest product-bearing carbonyl, carvone has been found in the seed essential oils of Anethum graveolens [9], Mentha spicata [10,11], and Carum 2 of 12 carvi [12], and its diverse pharmacological activities have been reported [13], such as antifungal [14][15][16][17], antioxidant [18], anti-inflammatory [19], and anticancer activities [20,21]. Moreover, it was discovered that the original skeleton of carvone could serve as an available pharmacophore for bioactive compounds [22][23][24][25][26]. Moreover, thiazolinone-hydrazone derivatives showed various biological activities, including antifungal [27], antitrypanosomal [28,29], insecticidal [30,31], antiproliferative [32], and α-glucosidase inhibition activities [33].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Carvone, a chiral ketone-bearing monocyclic monoterpene structure, is naturally found in various plant essential oils, 7 such as spearmint (Mentha spicata), 8,9 caraway (Carum carvi), 10 and dill (Anethum graveolens), 11 and it has been applied as a building block to construct some bioactive compounds. 12,13 Besides, according to the reported literature, [14][15][16] 1,2,4-triazole-thioether moiety could serve as a promising pharmacophore for the design, discovery, and development of new green herbicides. The study of Wang et al 14 revealed that transketolase (TK) was one of the potential biological targets for those herbicidal compounds containing a 1,2,4-triazole-thioether structure.…”
Section: Introductionmentioning
confidence: 99%
“…L(−)-carvone, a monoterpene insecticide, is environmentally friendly and effective in controlling pests [ 7 ]. Thus, carvone has been widely used for many years as an insecticide, fungicide, antioxidant, and plant growth regulator [ 8 , 9 , 10 , 11 ]. Carvone is widely used as a plant essential oil in the treatment of parasitic nematodes.…”
Section: Introductionmentioning
confidence: 99%